РУССКИЙ ЯЗЫК РОССИЙСКИХ БИЛИНГВОВ: ПРОБЛЕМЫ ФУНКЦИОНИРОВАНИЯ И МЕТОДЫ ОБУЧЕНИЯ (Philological Studies, 2019)
The article observes problems of bilingualism in Russia on the example of bilinguals in Perm krai. The comparison speech of Russian bilinguals and foreigners studying the Russian language demonstrates that mistakes in both cases are similar. The analysis of mistakes leads to the conclusion that it is necessary to modify methods of Russian language teaching of Russian bilinguals towards methods of foreign language teaching
Keywords: : bilingualism, Russian language, Russian bilinguals, Russian as a foreign language, teaching methods